2022
DOI: 10.1128/spectrum.02845-22
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Diversity of a Globally Used, Live Attenuated Mycoplasma Vaccine

Abstract: Preventative measures, such as vaccination, are commonly used for the control of mycoplasmal infections in poultry. A live attenuated vaccine strain (Vaxsafe MS; MS-H; Bioproperties Pty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Some mycoplasmas have been found to exhibit significant genetic plasticity and to evolve rapidly, mainly driven by intra-species spontaneous mutation and recombination or horizontal gene transfer (HGT) between and within species, facilitating swift adaptation to environmental changes, enhancing survival and/or virulence [ 6 9 ]. Studies examining the genomic stability of Mycoplasma synoviae have revealed that mutations occur frequently during infection in birds [ 10 ], and that rapid thermoadaptive evolution can occur in vitro and in vivo [ 11 ], presumably to regain fitness and pathogenicity [ 12 13 ]. HGT appears to occur more frequently between species that share an ecological niche, irrespective of their phylogenetic divergence.…”
Section: Introductionmentioning
confidence: 99%
“…Some mycoplasmas have been found to exhibit significant genetic plasticity and to evolve rapidly, mainly driven by intra-species spontaneous mutation and recombination or horizontal gene transfer (HGT) between and within species, facilitating swift adaptation to environmental changes, enhancing survival and/or virulence [ 6 9 ]. Studies examining the genomic stability of Mycoplasma synoviae have revealed that mutations occur frequently during infection in birds [ 10 ], and that rapid thermoadaptive evolution can occur in vitro and in vivo [ 11 ], presumably to regain fitness and pathogenicity [ 12 13 ]. HGT appears to occur more frequently between species that share an ecological niche, irrespective of their phylogenetic divergence.…”
Section: Introductionmentioning
confidence: 99%
“…Mycoplasmas are known for their rapid evolution and genetic plasticity, mainly driven by intraspecies spontaneous mutation or horizontal gene transfer (HGT) between and within species, facilitating swift adaptation to environmental changes and enhancing survival and/or virulence [6][7][8][9]. Studies examining the genomic stability of Mycoplasma synoviae revealed that it not only undergoes frequent mutations in birds [10], but also manifests rapid thermoadaptive evolution in vitro and in vivo [11], presumably to regain fitness and pathogenicity [12,13]. HGT is observed to occur more frequently between species that share an ecological niche irrespective of their phylogenetic divergence, such as transfer of surface VlhA lipoprotein involved in phase variation from Mycoplasma gallisepticum to M. synoviae infecting poultry [14], and transfer of several surface lipoproteins involved in host colonisation from Mycoplasma capricolum subsp.…”
Section: Introductionmentioning
confidence: 99%
“…Some mycoplasmas have been found to exhibit significant genetic plasticity and to evolve rapidly, mainly driven by intra-species spontaneous mutation and recombination or horizontal gene transfer (HGT) between and within species, facilitating swift adaptation to environmental changes, enhancing survival and/or virulence [6][7][8][9]. Studies examining the genomic stability of Mycoplasma synoviae have revealed that mutations occur frequently during infection in birds [10], and that rapid thermoadaptive evolution can occur in vitro and in vivo [11], presumably to regain fitness and pathogenicity [12,13]. HGT appears to occur more frequently between species that share an ecological niche, irrespective of their phylogenetic divergence.…”
Section: Introductionmentioning
confidence: 99%